Symmetric identities for the fully degenerate bernoulli polynomials and degenerate euler polynomials under symmetric group of degree n - Kim, Taekyun,; Kwon, Hyuck-In,; Mansour, Toufik,; Rim, Seog-Hoon, (Utilitas Mathematica, 2017)
In this paper, we present some new identities of symmetry for the fully degenerate Bernoulli polynomials and degenerate Euler polynomials under symmetric group of degree n arising from p-Adic q-integrals on Zp. © 2015 Utilitas Mathematics.